Comparison of screening strategies for Lynch syndrome in patients with newly diagnosed endometrial cancer: a prospective cohort study in China. Issue 1 (15th July 2019) - Chao, Xiaopei; Li, Lei; Wu, Ming; Ma, Shuiqing; Tan, Xianjie; Zhong, Sen; Bi, Yalan; Lang, Jinghe
Abstract: Background: The prevalence of Lynch syndrome and screening strategies for this disorder in Chinese patients with endometrial cancer have seldom been investigated. Such data would be essential for the screening, prevention, genetic counseling, and treatment of Lynch syndrome. The purpose of this prospective study was to determine the accuracy of the mismatch repair (MMR) protein immunohistochemistry (IHC), microsatellite instability (MSI) test, and clinical diagnostic criteria in screening for Lynch syndrome‐associated endometrial cancer (LS‐EC) in a prospective Chinese cohort. Methods: All patients with newly diagnosed endometrial cancer (EC) were evaluated using clinical diagnostic criteria (Amsterdam II criteria and the revised Bethesda guidelines), MSI test, and IHC of MMR proteins in tumor tissues. For all patients, the screening results were compared with results of germline sequencing for pathogenic variants of MMR genes. Results: Between December 2017 and August 2018, a total of 111 unselected patients with newly diagnosed EC were enrolled. Six patients (5.4%) harbored a pathogenic germline mutation of MMR genes: 1 had a mutation in MutL homolog 1 ( MLH1 ), 2 in MutS homolog 2 ( MSH2 ), and 3 in MutS homolog 6 ( MSH6 ). The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) for identifying LS‐EC were 33.3%, 88.6%, 14.3%, and 95.9%, for the clinical criteria, 66.7%, 75.0%, 14.3%, and 97.3% for IHC of MMR proteins, 100%, 89.9%, 33.3%, and 100% for MSI test, and 100%, 72.4%, 20.0% and 100% for combined IHC and MSI test, respectively. The combination of IHC and MSI test had higher sensitivity and PPV than the clinical criteria ( p = 0.030). MSI test and IHC were highly concordant for LS‐EC screening (73/77, 94.8%). Conclusion: The accuracy of the combination of IHC of MMR proteins and MSI test for screening LS among Chinese patients with EC was superior to that of the clinical criteria. Trial registration NCT03291106. Registered on September 25, 2017